2013
DOI: 10.1002/cbf.3007
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of Krüppel‐like factor 4 on X‐ray‐induced double‐strand and single‐strand DNA breaks in mouse astrocytes

Abstract: Astrocytes, the most common cell type in the brain, play a principal role in the repair of damaged brain tissues during external radiotherapy of brain tumours. As a downstream gene of p53, the effects of Krüppel-like factor 4 (KLF4) in response to X-ray-induced DNA damage in astrocytes are unclear. In the present study, KLF4 expression was upregulated after the exposure of astrocytes isolated from the murine brain. Inhibition of KLF4 expression using lentiviral transduction produced less double-strand DNA brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In this model however, KLF4 is not essential for CDKN1A expression in the intestinal epithelium following total body γ-irradiation. In contrast to the role of KLF4 following γ-irradiation exposure, exposure of murine astrocytes to X-ray radiation upregulates KLF4 expression, which induces more double-strand DNA breaks (DSB), less single-strand breaks (SSB) and increases apoptosis (162). This is intriguing because there is evidence that under certain conditions repairable single-strand breaks may not result in cell death, while irreparable DSB are deemed lethal events, and where it was also shown that in some systems, the ratio of SSB to DSB are crucial in determining which death pathway the cell may undertake (163165).…”
Section: Roles In Diseasesmentioning
confidence: 99%
“…In this model however, KLF4 is not essential for CDKN1A expression in the intestinal epithelium following total body γ-irradiation. In contrast to the role of KLF4 following γ-irradiation exposure, exposure of murine astrocytes to X-ray radiation upregulates KLF4 expression, which induces more double-strand DNA breaks (DSB), less single-strand breaks (SSB) and increases apoptosis (162). This is intriguing because there is evidence that under certain conditions repairable single-strand breaks may not result in cell death, while irreparable DSB are deemed lethal events, and where it was also shown that in some systems, the ratio of SSB to DSB are crucial in determining which death pathway the cell may undertake (163165).…”
Section: Roles In Diseasesmentioning
confidence: 99%
“…In vitro doses ≥2 Gy can cause apoptosis, while in vivo , this occurs at ≥6 Gy (Chatterjee et al, 2018; Lagroye and Poncy, 1997). Doses of 1 and 2 Gy can cause a decrease in neuron proliferation (Hudson et al, 2011), whereas 2 Gy can cause significant DNA damage (Chatterjee et al, 2018; Nairy et al, 2015) with more than 90% of proliferating (tumor) cells in the adult mice brain going into apoptosis and can lower the rate of tumor cell repair (Zhao et al, 2019) with most of SSB repaired within 48 h of exposure (El-Nahas et al, 1993; Mut et al, 2004) and residual damage considered to be DSB (Benitez-Bribiesca and Sanchez-Suarez, 1999; Mut et al, 2004; Olive, 1998; Zhang et al, 2014). This approach is also used in RT.…”
Section: Discussionmentioning
confidence: 99%
“…Research in resveratrol has found that KLF4 and early growth response-1 expression was increased by resveratrol, resulting in transcription factor 3 activation and cellular apoptosis [ 30 ]. KLF4 expression is increased in murine astrocytes when exposed to X-ray radiation, resulting in more double-strand DNA breaking, and at last cell apoptosis [ 31 ]. The apoptosis rate of SK-BR-3 breast cancer cells is increased and cell tumorigenicity is decreased by upregulation of KLF4 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%